Analisis Implementasi Sosialisasi Pemberian Asi Eksklusif Oleh Bidan Praktek Swasta (BPS) Di Kabupaten Bengkulu Selatan - Lela Hartini; Martha Irene Kartasurya; Susi Herawati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Profile of South Bengkulu district health office 2008 – 2009 did not include data on exclusive breastfeeding coverage. Private practice midwives (BPS) did not have standard operating procedure (SOP) in providing obstetric service. One of midwives duties was to provide exclusive breastfeeding socialization to pregnant women, childbearing mothers and community. The objective of this study was to analyze the implementation of exclusive breastfeeding socialization by BPS in South Bengkulu district. This study applied qualitative method and using in-depth interview as data collection technique. The main informant was 3 private practice midwives in the city area and 2 private practice midwives in the rural area. Triangulation was done to 5 head of puskesmas, chief of nutritional unit and head of Indonesian Midwifery Association (IBI). Focus group discussion was conducted to 3 mothers and 3 people in the community (family member of the patient) in each selected BPS. Results of the study showed that implementation of exclusive breastfeeding socialization variable was still limited to individual education and no education materials were provided. There was no communication among head of puskesmas, head of district health office and head of IBI towards BPS. BPS facilities were still insufficient to support the success of exclusive breastfeeding. Disposition had not supported exclusive breastfeeding coverage improvement. In the bureaucracy structure variable, there was no reporting format from BPS to puskesmas on exclusive breastfeeding socialization implementation in South Bengkulu district. It was suggested to district health office to formulate regulation policy in the form of decree regarding exclusive breastfeeding and to forbid collaboration between BPS and infant formula companies. Head of puskesmas had to do supervision and monitoring to BPS. Private practice midwives were expected to improve the frequency of exclusive breastfeeding socialization and to avoid collaboration with infant formula companies.